Evaluation of allergic rhinitis and asthma control in a Portuguese community pharmacy setting - Lourenço, Olga (2014)
BACKGROUND: Allergic rhinitis and asthma (ARA) are frequent respiratory diseases that often coexist, causing a high social and economic impact. It is important to maintain ARA disease control to reduce the disease burden. OBJECTIVE: To assess control in patients with 1 or both pathologies through the application of validated questionnaires at community pharmacies. METHODS: A cross-sectional study was conducted in the pharmacies of the Portuguese county of Covilhã (located in the central region of Portugal with about 53,000 inhabitants). Subjects aged between 18 and 70 years who presented a prescription for an asthma and/or allergic rhinitis medication were invited to participate in the study by responding to a questionnaire that included the Control of Allergic Rhinitis and Asthma Test (CARAT). The CARAT is a validated tool to simultaneously assess the control of ARA with scores that range from 0 to 30 points, 0 meaning the worst and 30 meaning the best possible control of disease. RESULTS: Of the 224 participants, 58% were female and the median age was 48.5 years. The median CARAT score was 19 (mean = 17.8 ± 5136.4), and 87% of participants had a score < 25, indicating noncontrolled disease. Female participants, the elderly, and those with less school education responded with scores that demonstrated significantly less disease control. CONCLUSIONS: Using a simple self-assessment questionnaire, such as the CARAT, pharmacists can help identify patients with uncontrolled ARA disease, which is an important first step to change patients’ knowledge about their disease, with an ultimate goal of improving ARA outcomes.